2022
DOI: 10.21203/rs.3.rs-1318567/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The early impacts of COVID-19 on unpaid carers of people living with dementia: Part II of a mixed-methods systematic review

Abstract: Background With a lack of existing comprehensive reviews, the aim of this mixed-methods systematic review was to synthesise the evidence on the early impacts of the pandemic on unpaid dementia carers across the globe. Methods This review was registered on PROSPERO [CDR42021248050]. PubMed, CINAHL, Embase, Scopus and Web of Science were searched from 2020 to July 2021. Studies were included if they reported on the different impacts of the pandemic on unpaid dementia carers aged 18+, with papers published in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Adopting a social inclusion lens, we found that many carers, irrespective of their socio‐demographic characteristics, employed ICTs, and to a lesser extent ATs, at the start of the UK lock‐down. Interestingly there were limited discussions around the use of digital gaming devices during this period, which may suggest, as other research has posited, that currently this is something rarely considered by people with dementia and their carers (due to fear, lack of knowledge or belief it is unsuitable for them) or promoted in the dementia care agenda 26–29 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Adopting a social inclusion lens, we found that many carers, irrespective of their socio‐demographic characteristics, employed ICTs, and to a lesser extent ATs, at the start of the UK lock‐down. Interestingly there were limited discussions around the use of digital gaming devices during this period, which may suggest, as other research has posited, that currently this is something rarely considered by people with dementia and their carers (due to fear, lack of knowledge or belief it is unsuitable for them) or promoted in the dementia care agenda 26–29 …”
Section: Discussionmentioning
confidence: 96%
“…In late 2019, a new coronavirus (COVID‐19) emerged causing global disruption and stringent restrictions on social contact, activities and service provision, resulting in adverse impacts particularly on the well‐being, burden and support capabilities of family carers of people with dementia 23–26 . It also triggered rapid and unprecedented changes in the use of digital technologies throughout society 27 as these became essential for many people to sustain social connection 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Much of what participants reported concerning the impact of the pandemic was congruent with reports from the wider health and social care landscape. For example, the impact pandemic-instigated isolation had upon people affected by dementia and the accelerated decline they experienced as a result (Alzheimer’s Society, 2020; Age UK, 2021; Giebel et al , 2022a, 2022b); and continuing difficulties with delays and access to health and social care support, as services struggle to recover (Bhome et al , 2021; Britton and Zimmerman, 2022; CQC, 2022). The difficulties reported by participants in recruiting staff are reflected in UK-wide data, with a recent House of Commons report stating: “The National Health Service and the social care sector are facing the greatest workforce crisis in their history.” (UK Parliament, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For those living at home in the community, social opportunities and formal support were severely curtailed during successive lockdowns, with the suspension or reduction of community services and difficulty in accessing health services (Alzheimer’s Society et al , 2021; Pentecost, 2022). This is internationally reported to have increased carer burden, led to faster cognitive, physical and behavioural decline for those with dementia, and impacted mental health for both (Giebel et al , 2022a, 2022b).…”
Section: Introductionsmentioning
confidence: 99%
“… 17 In fact, many unpaid informal caregivers experienced a significant burden of caregiving and poor mental health long before the novel coronavirus pandemic. 18 During the pandemic, many medical workers focused on pandemic spread prevention and control and patient treatment, while less attention was devoted to the mental health and well-being of informal caregivers within the hospital. 19 Furthermore, approximately 50% of informal caregivers reported an elevated informal caregiver burden during the pandemic.…”
Section: Introductionmentioning
confidence: 99%